Cone-Beam Computed Tomographic Assessment of Mandibular Condylar Position in Patients with Temporomandibular Joint Dysfunction and in Healthy Subjects - Maryam Paknahad; Shoaleh Shahidi; Shiva Iranpour; Sabah Mirhadi; Majid Paknahad (International Journal of Dentistry)
Statement of the Problem. The clinical significance of condyle-fossa relationships in the temporomandibular joint is a matter of controversy. Different studies have evaluated whether the position of the condyle is a predictor of the presence of temporomandibular disorder. Purpose. The purpose of the present study was to investigate the condylar position according to gender in patients with temporomandibular disorder (TMD) and healthy controls using cone-beam computed tomography. Materials and Methods. CBCT of sixty temporomandibular joints in thirty patients with TMD and sixty joints of thirty subjects without TMJ disorder was evaluated in this study. The condylar position was assessed on the CBCT images. The data were analyzed using Pearson chi-square test. Results. No statistically significant differences were found regarding the condylar position between symptomatic and asymptomatic groups. Posterior condylar position was more frequently observed in women and anterior condylar position was more prevalent in men in the symptomatic group. However, no significant differences in condylar position were found in asymptomatic subjects according to gender. Conclusion. This study showed no apparent association between condylar positioning and clinical findings in TMD patients.